SATIRE WARGANET YOUTUBE MATA NAJWA GANJAR PRANOWO BICARA GAGASAN: ANALISIS WACANA KRITIS TEUN A VAN DIJK - Khusnul Khotimah; Ali Nuke Affandy; Ngatma’in Ngatma’in (Universitas Negeri Makassar, 2024)
The purpose of this research is to describe the netizen comments in Mata Najwa Ganjar Pranowo Bicara Gagasan youtube using Teun A Van Dijk's critical discourse analysis theory used in satire language. This research is a qualitative research that uses descriptive method. The data used are sentences containing satire in Mata Najwa Bicara Gagasan youtube comments with Teun A Van Dijk's critical discourse analysis theory. Based on van dijk's discourse structure, there are three text structures, namely, macro structure, super structure and micro structure. Macro structure is the main idea or summary in the text, the second super structure is a schematic structure that includes title, introduction, content, and conclusion. The third micro structure in this structure there are semantic elements that are observed, namely, setting, details, intent, and presumption. The second is syntactic elements observed coherence, sentence form, and pronouns and the third is stylistic elements observed lexicon and the fourth is rhetorical elements observed graphics, metaphors and graphs.